PENGAWASAN DAN PERLINDUNGAN KONSUMEN DALAM TRANSAKSI BISNIS E-COMMERCE DI INDONESIA - Putu Eka Trisna Dewi (Fakultas Hukum Universitas Ngurah Rai, 2019)
Rapidly developing technology now has a big impact on business activities. The advent of the internet as a technological development can connect the world without limits. In business activities, technological developments are marked by the emergence of trading activities in cyberspace known as e-commerce. This research is a normative legal research with a library research. This study also uses a statute approach. Intense trade competition has given consumers an advantage in online transactions, especially in getting goods and services that are easier and cheaper. However, in this e-commerce transaction there are also many risks and fraud that occur to consumers, causing various legal problems.